Analisis Laporan Keuangan dalam Mengukur Kinerja Keuangan pada PT Bank Sulselbar Laporan Tahunan Periode 2021-2023 (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze financial statements in measuring financial performance at PT Bank Sulselbar based on the annual report for the period 2021-2023. This study uses a quantitative descriptive analysis method with a case study approach at PT Bank Sulselbar. The data used are secondary data obtained from the company's annual financial statements during the study period. The data analysis techniques used include financial ratio analysis, namely liquidity ratio, solvency, profitability, and activity to assess the bank's overall financial condition and performance.The results of the study show that in general the financial performance of PT Bank Sulselbar in the period 2021-2023 is in the good category based on the results of the financial ratio analysis. The liquidity ratio shows the bank's ability to meet short-term obligations at a healthy level. The solvency ratio indicates that the company is able to meet its long-term obligations. The profitability ratio shows an increase in profit generated from operational activities, while the activity ratio shows the efficiency of asset use in generating income. Thus, it can be concluded that PT Bank Sulselbar is able to maintain its financial performance well during the study period.